2022
DOI: 10.1371/journal.pgen.1010478
|View full text |Cite
|
Sign up to set email alerts
|

Education interacts with genetic variants near GJD2, RBFOX1, LAMA2, KCNQ5 and LRRC4C to confer susceptibility to myopia

Abstract: Myopia most often develops during school age, with the highest incidence in countries with intensive education systems. Interactions between genetic variants and educational exposure are hypothesized to confer susceptibility to myopia, but few such interactions have been identified. Here, we aimed to identify genetic variants that interact with education level to confer susceptibility to myopia. Two groups of unrelated participants of European ancestry from UK Biobank were studied. A ‘Stage-I’ sample of 88,334… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 70 publications
(79 reference statements)
0
18
0
Order By: Relevance
“…Josh Wallman pointed out that the effect could possibly as well be explained if myopic parents, who are more likely to be wealthier and better educated, create more myopigenic environments [ 28 ]. Recently, Guggenheim has also suggested that genetic effects explain only part of the impact of parental myopia [ 29 ]. Currently, hundreds of genetic loci have been identified for refractive error and myopia, and risk variants mostly carry low risk but are highly prevalent in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Josh Wallman pointed out that the effect could possibly as well be explained if myopic parents, who are more likely to be wealthier and better educated, create more myopigenic environments [ 28 ]. Recently, Guggenheim has also suggested that genetic effects explain only part of the impact of parental myopia [ 29 ]. Currently, hundreds of genetic loci have been identified for refractive error and myopia, and risk variants mostly carry low risk but are highly prevalent in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely acknowledged that the discovery of interaction effects is much more difficult than finding genetic or environmental marginal effects 67 . Previously published results have seldom been replicated 12–14,19,22,23,25,26,28,31,35 . To the best of our knowledge, an interaction between GJD2 (rs524952) and near‐work burdens has been identified by two separate studies from different ethnicities 13,23 .…”
Section: Lack Of Replicationmentioning
confidence: 96%
“…A recent study applied a two‐stage approach and found five variants near GJD2, FBFOX1, LAMA2, KCNQ5 and LRRC4C that could interact with educational level and the risk effects of these variants increased with additional years of education 26 …”
Section: Genome‐wide Association Studies × Environmentmentioning
confidence: 99%
See 2 more Smart Citations